Search for first generation leptoquarks in ep collisions at HERA - Aaron, Francisc Dionisie; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (Physics letters, 2011)
A search for first generation scalar and vector leptoquarks produced in ep collisions is performed by the H1 experiment at HERA. The full H1 data sample is used in the analysis, corresponding to an integrated luminosity of 446 pb−1. No evidence for the production of leptoquarks is observed in final states with a large transverse momentum electron or with large missing transverse momentum, and constraints on leptoquark models are derived. For leptoquark couplings of electromagnetic strength λ=0.3, first generation leptoquarks with masses up to 800 GeV are excluded at 95% confidence level.
*H1 Collaboration: F.D. Aaron, H. Pirumov, M. Sauter, A. Schoening, H.-C. Schultz-Coulon [und 198 weitere Personen]
Gesehen am 23.02.2022